Pembelajaran Qur’an Hadits di MI YAPPI Tambakromo Gunungkidul - Noviati Noviati; Ria Nurhayati (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2023)
Al-Qur'an Hadith learning at MI-level religious schools must be following a predetermined curriculum, with the aim that students know, understand and believe, and practice the verses of the Al-Qur'an Hadith perfectly. For these goals to be achieved, the learning process must run as it should. The learning process of Al-Qur'an Hadith at MI YAPPI Tambakromo consists of several stages of usual learning, namely the planning stage, the learning process, and the assessment. Learning is influenced by several factors, such as teachers, students, environment, and infrastructure. This article aims to discuss Class V Qur'an Hadith learning at MI YAPPI Tambakromo which focuses on 3 (three) stages of learning, planning, implementation, and assessment as well as the obstacles encountered. This research is qualitative. Data collection techniques using interviews, observation, and documentation. The results are showed that the Al-Qur'an Hadith learning planning activities at MI YAPPI Tambakromo were quite good. The implementation of learning activities at MI YAPPI Tambakromo refers to the lesson plans made at the beginning of the semester, although there has been a slight change in the points of learning media due to adjusting school facilities and infrastructure. The assessment of Al-Qur'an Hadith learning activities at MI YAPPI Tambakromo has been carried out as it should be according to the 2013 Curriculum guidelines. But one assessment is not available at MI YAPPI Tambakromo, that is assessment of the placement function.